Spirit-Filled World Religious Dis/Continuity in African Pentecostalism - Anderson, Allan Heaton (Christianity and Renewal - Interdisciplinary Studies, 2018)
This book is about African Pentecostalism and its relationship to religious beliefs about a pervading spirit world. It argues that Pentecostalism keeps both a continuous and a discontinuous relationship in tension. Based on field research in a South African township, including qualitative interviews and focus group discussions, the study explores the context of African Pentecostalism as a whole and how it interacts with the concepts of ancestors, divination, and various types of spirit. Themes discussed include the reasons for the popularity of healing, exorcism, the "prosperity gospel," the experience of the Holy Spirit, Spirit manifestations and practices resembling both traditional and biblical precedents, as well as scholarly discussions on African Pentecostalism from theological and social scientific disciplines. The book suggests that the focus on a spirit-filled world affects all kinds of events and explains the rapid growth of Pentecostalism outside the western world.